USB powered microfluidic paper‐based analytical devices. Issue 7 (8th November 2019) - Schaumburg, Federico; Kler, Pablo A.; Carrell, Cody S.; Berli, Claudio L. A.; Henry, Charles S.
Abstract: Microfluidic paper‐based analytical devices (μPADs) allow user‐friendly and portable chemical determinations, although they provide limited applicability due to insufficient sensitivity. Several approaches have been proposed to address poor sensitivity in μPADs, but they frequently require bulky equipment for power and/or read‐outs. Universal serial buses (USB) are an attractive alternative to less portable power sources and are currently available in many common electronic devices. Here, USB‐powered μPADs (USB μPADs) are proposed as a fusion of both technologies to improve performance without adding instrumental complexity. Two ITP USB μPADs were developed, both powered by a 5 V potential provided through standard USB ports. The first device was fabricated using the origami approach. Its operation was analyzed experimentally and numerically, yielding a two‐order‐of‐magnitude sample focusing in 15 min. The second ITP USB μPAD is a novel design, which was numerically prototyped with the aim of handling larger sample volumes. The reservoirs were moved away from the ITP channel and capillary action was used to drive the sample and electrolytes to the separation zone, predicting 25‐fold sample focusing in 10 min. USB μPADs are expected to be adopted by minimally‐trained personnel in sensitive areas like resource‐limited settings, the point‐of‐care and in emergencies.